3(x-2)+5=6x-5

Simple and best practice solution for 3(x-2)+5=6x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)+5=6x-5 equation:



3(x-2)+5=6x-5
We move all terms to the left:
3(x-2)+5-(6x-5)=0
We multiply parentheses
3x-(6x-5)-6+5=0
We get rid of parentheses
3x-6x+5-6+5=0
We add all the numbers together, and all the variables
-3x+4=0
We move all terms containing x to the left, all other terms to the right
-3x=-4
x=-4/-3
x=1+1/3

See similar equations:

| (a-4)/2=-5 | | 2(c+1=c-7 | | 11y+2=y | | 7/15=1.4x | | 11y+5-y=y | | 7/15=1(2/5)x | | 7/15=12/5x | | 3/2y=0 | | 2.12=p/8 | | 5x-1=3(x+5) | | 12^x=1 | | 2.12=p/12 | | (10+x)(12+x)=240 | | 4x=5=1 | | 3x/4x-1=14/18 | | 4x-13=-33 | | F(x)=3x^2+7x+7F(-2) | | F(x)=3x^2+7x+7 | | x^2+2√3x-34=0 | | F(-2)=3x^2+7x+7 | | 2(p=1)=16 | | -8x+16=3x+5 | | -8x+16=3x÷5 | | -7+8a-8a=1+3a+7 | | x^2=441^-1 | | 21a=30 | | 1+k=-1-k | | 25-5x=9x | | x^2-2x+3x-6=2x-4 | | 3^x^-2=10 | | 14x-13=4+8x= | | -8x^2+8x=6 |

Equations solver categories